Does Corporate Governance Increase Shareholder Value? - Ganesan, Anushia (2005)
This dissertation attempts to answer the question of “Does Corporate Governance Improve Shareholder Value?” by using a simple statistical analysis of correlation to evaluate the importance of corporate governance to shareholder value. In addition this study also aims to evaluate the extent of this relationship and to recommend better ways to improve shareholder value. Data was obtained from two studies. The first study used is the 2003 KPMG/The Edge Annual Shareholder Values. This report provided the top 100 companies listed on the Bursa Malaysia that had the highest shareholder value. The second study used is the MSWG-NUBS Malaysian Corporate Governance ranking. This study in turn lists the top 100 companies that scored high in the Corporate Governance ranking. This study only concentrates on the top 100 companies with the highest market capitalization, listed on the Bursa Malaysia. The findings were contrary to popular literature on this subject, where this study found that corporate governance did not have an impact on shareholder value creation. In fact most of the companies that ranked high on the corporate governance ranking did well below average in the shareholder value ranking.